2007
DOI: 10.1016/j.febslet.2007.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic c‐H‐ras deregulates survivin expression: An improvement for survival

Abstract: Survivin protein accomplishes two basic functions: cell cycle regulation and control of apoptosis. It is only expressed in G2/M phase and it influences rescue pathways in apoptosis-induced cells. Overexpression of constitutive active c-H-ras in HeLa, or induction of c-H-ras in a stable HeLaDiR cell line, led to sustained survivin expression in all cell cycle phases and even protected cells from drug induced apoptosis. siRNA-mediated silencing of survivin reversed this protection. Here we link the anti-apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…After checking survivin depletion by Western Blot analysis, we found that the expression of Ha-Ras G12V -IκBαM in keratinocytes promoted survivin upregulation ( Figure 3 A), which is in line with the induction of the oncogenic phenotype in keratinocytes and the higher level of survivin in cancer cells [ 42 ]. This is also in agreement with Ras-dependent upregulation of survivin in HaCaT cells [ 43 , 44 ] and normal K-Ras promoted survivin degradation [ 45 ].…”
Section: Resultssupporting
confidence: 83%
“…After checking survivin depletion by Western Blot analysis, we found that the expression of Ha-Ras G12V -IκBαM in keratinocytes promoted survivin upregulation ( Figure 3 A), which is in line with the induction of the oncogenic phenotype in keratinocytes and the higher level of survivin in cancer cells [ 42 ]. This is also in agreement with Ras-dependent upregulation of survivin in HaCaT cells [ 43 , 44 ] and normal K-Ras promoted survivin degradation [ 45 ].…”
Section: Resultssupporting
confidence: 83%
“…Therefore, K-Ras is necessary for the maintenance of survivin but not sufficient to increase survivin levels. Whether ectopic expression of CA-H-Ras can increase survivin levels is not clear, with some studies showing that it can 14,15 and another showing that it cannot. 16 In addition to depleting the endogenous levels of survivin, our studies also demonstrated that depletion of K-Ras was able to decrease the levels of exogenous survivin whose ectopic expression was under the control of a foreign promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that, ectopic overexpression of c-H-Ras in rat cells as well as in human keratinocytes induces survivin expression. 13,14 Furthermore, Fukuad et al showed that exogenous H-Ras is required for interleukin induced survivin in Baf-3 cells. 15 However, other studies showed that mutant H-Ras is not able to increase survivin.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these data, Suzuki et al (2000) demonstrated that Survivin might play an important role in early cell cycle entry by activating both Cdk4/cyclinD and Cdk2/CyclinE complexes linked to the release of their respective inhibitors p21 Waf1 and p16 INK4a from these complexes. Of note, activated mutants of the oncogene NRAS were able to induce IL6‐independent myeloma cell growth (Billadeau et al , 1995) and to deregulate Survivin expression (Sommer et al , 2007). It is therefore tempting to hypothesize that NRAS may interfere with the IL6 pathway to regulate BIRC5 expression.…”
Section: Discussionmentioning
confidence: 99%